Enantioselective determination of carboxyl acid amide fungicide mandipropamid in vegetables and fruits by chiral LC coupled with MS/MS. Issue 3 (13th December 2013) - Zhang, Hu; Wang, Xiangyun; Wang, Xinquan; Qian, Mingrong; Xu, Mingfei; Xu, Hao; Qi, Peipei; Wang, Qiang; Zhuang, Shulin
Abstract : An efficient enantioselective method for the determination of mandipropamid in vegetables and fruits was presented by LC coupled with MS/MS. The mandipropamid residues in samples (potato, pepper, grape, and watermelon) were extracted with acetonitrile containing 1% acetic acid. An aliquot was cleaned up with primary and secondary amine and C18 sorbent. Complete enantioseparation of mandipropamid enantiomers in <4 min was obtained on a Lux Cellulose‐2 column at 25°C using methanol with 0.1% formic acid/0.1% aqueous formic acid solution (85:15, v/v) as mobile phase. Good linearity was obtained over the concentration range of 0.5–250 μg/L for each enantiomer in the standard solution and sample matrix calibration curves. Quantification was achieved using matrix‐matched standard calibration curves. The interday mean recoveries, intraday repeatability, and inter‐day reproducibility varied from 76.4 to 97.1%, 3.4 to 9.4%, and 3.5 to 11.4%, respectively. The limits of quantification for mandipropamid enantiomers in vegetables and fruits were both 1 μg/kg. Moreover, the absolute configuration of mandipropamid enantiomers was determined by the combination of experimental and predicted electronic circular dichroism spectra, and the first eluted enantiomer was confirmed as ( R )‐mandipropamid on five chiral columns.